Effect of temperature on elementary steps of the cross-bridge cycle in rabbit soleus slow-twitch muscle fibres - Wang, Gang (Blackwell Science Inc, 2001)
1. Isometric tension, stiffness and the cross-bridge kinetics in rabbit soleus slow-twitch fibres (STFs) were studied in the temperature range 5–37°C by sinusoidal analysis. 2. The effects of MgATP and phosphate (P(i)) on the cross-bridge kinetics were studied, and the temperature dependence of the kinetic constants of elementary steps of the cross-bridge cycle was deduced in the range 20–37°C. 3. The MgATP association constant (K(1a)) decreased when temperature was increased. The rate constants of the ATP-isomerization step (k(1b) and k(−1b)) and the cross-bridge detachment step (k(2), and k(−2)) had Q(10) values of 3–4, and hence their equilibrium constants (K(1b) and K(2)) changed little with temperature. 4. Q(10) of the force generation step (k(4)) was the largest at 6.7; its reversal step (k(−4)) had a Q(10) of 2.5, and hence its equilibrium constant (K(4)) increased significantly with temperature. The P(i) association constant (K(5)) changed little with temperature. 5. The elementary steps of the cross-bridge cycle are more temperature sensitive in soleus STFs than in psoas, which are fast-twitch fibres. This is in accord with a higher temperature sensitivity of the apparent rate constants in STFs. 6. The temperature dependence of the equilibrium constant of the force generation step (K(4)) was fitted to the modified Van't Hoff equation to deduce standard enthalpy change (ΔH°; 70 ± 20 kJ mol(−1)), standard entropy change (ΔS°; 250 ± 70 J mol(−1) K(−1)), and heat capacity change (ΔC(p); −12 ± 5 kJ mol(−1) K(−1)). These results indicate that the force generation step is an entropy driven, endothermic reaction that accompanies a burial of large surface area. These observations are consistent with the hypothesis that hydrophobic interaction between residues of actin and myosin and between residues of the myosin head underlies the mechanism of force generation. 7. An increase of isometric tension with temperature is accounted for by the increased number of cross-bridges in tension generating states. Stiffness also increased with temperature, but to a lesser degree.